Design and development of a hand-glove controlled wheel chair - Akmeliawati, Rini; Ba Tis, Faez S.; J. Wani, Umar (2011)
Wheelchairs are a way of reincarnating the purpose of life in the lives of disabled people. Effective and efficient ways of delivering a cost-effective and affordable wheelchair to the common masses, which is not only at par with the present day technology, but is much easier to use are presented herewith. Replacement of the popular joystick stick controlled wheel chair with a hand-glove control system for easier maneuvering by bending the fingers, is discussed in this paper. Intended users control the system by wearing an instrumented glove fitted with flex or bend sensors for controlling the movement and direction of the wheelchair. Uni-directional wireless communication exists between the instrumented gloves and the controller which is sandwiched between the user’s seat and the wheels. Initial design results are also presented in this paper. The technologies presented in this paper suggest a wide domain of possibilities to a wide variety of users. In addition, it also aims at making a costeffective chair so that more hi-tech wheelchairs are made use of, widely, by people with disabilities.